The efficacy taro leaf extract on wound healing contaminated with Staphylococcus aureus - Sjamsudin, Endang; Muharty, Annisya; Riawan, Lucky; Priosoeryanto, Bambang Pontjo (Padjadjaran Journal of Dentistry, 2021)
Introduction: Taro (Colocasia esculenta (L.) Schott) leaves have been reported to possess wound healing, anti-inflammatory, antibacterial and antioxidant activities. One of the factors that affect wound healing is infection in the wound, wherein the wound is infected by  bacteria, especially Staphylococcus aureus that is mostly found in the oral cavity, the wound healing process will be hampered and become longer healed. The objective of this research was to analyse the efficacy of Colocasia esculenta (L.) Schott extract on the healing process of wounds contaminated with Staphylococcus aureus. Methods: This experimental study on Sprague dawley rats was carried out at the Veterinary Medical Teaching Hospital of the Faculty of Veterinary Medicine of IPB University. Circular excision wounds were applied on 24 Sprague dawley rats with a diameter of 2 cm on the dorsum, and Staphylococcus aureus specimens were contaminated with a dose of 3.4x108 LAC. Rats were randomly divided into 2 groups. Group I (control group) was given a placebo, and group II (treatment group) was given a 25% concentration of Colocasia esculenta (L.) Schott extract on the wound once a day. Four rats from each group were euthanized on the 3rd, 7th, and 14th days. The number of neutrophils, macrophages, re-epithelialization and FGF-2 expression were measured by microscopic observation with visual field control, and comparative data were analysed using the Kruskal-Wallis statistical test. Results: The number of neutrophils on the treatment group on the 7th day was less than the control group (p=0.040). The number of macrophages on the 3rd day was found more in the treatment group than the control group (p=0.032), and on the 14th day, the treatment group was less than the control group (p=0.040). Epithelial cells on the 14th day of the treatment group was found more than the control group (p=.0.017). The level of FGF-2 expression of the treatment group on the 7th day was higher than the control group (p=0.044). Conclusion: Application of Colocasia esculenta (L.) Schott leaf extract is efficacious for healing wounds contaminated with Staphylococcus aureus in the proliferative phase.